Diaspora Mobilization for Western Military Intervention During the Arab Spring. Issue 3 (2nd July 2016) - Moss, Dana M.
ABSTRACT: Literature on diaspora interest groups suggests that they exacerbate home-country conflicts by lobbying for hawkish interventions. However, studies fall short of understanding why diasporas support militarized interventions in home-country conflicts. Using original data on Libyan and Syrian pro-revolution activism during the Arab Spring, I demonstrate that extreme escalations in state repression, activists' transnational ties, and norms supporting the "responsibility to protect" produced perceptions that militarized interventions were necessary countermeasures to mass killings. Overall, analyses of diasporas' orientations to home-country conflicts should account for annihilative threats to populations at home, diasporas' relations with those on the ground, and humanitarian intervention norms.